Investigating the Effectiveness of a Mindfulness-Based Acceptance Training Package on Mother-Child Relationships in Children with Autism Spectrum Disorder - Ofoghi , Haleh; Amini Manesh, Sajad; Mozafari, Mohammad; Bardideh, Mohammadreza (Psychology of Woman Journal, 2025)
Objective: This study aimed to examine the effectiveness of a mindfulness-based acceptance training package on the mother-child relationship in mothers of children with ASD. Methods and Materials: This quasi-experimental study employed a pretest-posttest design with a control group. The statistical population included mothers of children with ASD attending the Special Needs Children Training and Research Clinic at Shahid Beheshti University in Tehran. Using convenience sampling, 30 mothers were selected and randomly assigned to the experimental and control groups (15 participants each). The experimental group received 12 sessions of a mindfulness-based acceptance training package, each lasting 120 minutes, while the control group received no training. Both groups completed the Parent-Child Relationship Scale (Driscoll & Pianta, 2011) before and after the intervention. Data analysis was performed using covariance matrix analysis in SPSS software version 27. Findings: Results revealed a significant difference in the overall positive parent-child relationship between the experimental group, which received the mindfulness-based acceptance training package, and the control group (P < 0.001). Additionally, the effect of the intervention remained stable during the follow-up phase (P < 0.001). Conclusion: Based on the findings, it can be concluded that the mindfulness-based acceptance training package improves the mother-child relationship in families with children with ASD. Therefore, this training package can be utilized to enhance the relationship between mothers and their children with ASD.